Cardiac Rhabdomyoma in Children - Ye.V. Bordyugova; A.V. Dubovaya; A.A. Burka; I.Yu. Mokrik; O.S. Kartashova (Zaslavsky O.Yu., 2012)
In the article there are presented the results of clinical supervision of 15 children with cardiac rhabdomyoma revealed in Institute of urgent and reconstructive surgery named after V.K. Gusak of NAMS of Ukraine from March 2007 till May 2011. The combination of disease with tuberous sclerosis, diagnostics of a tumor with ingrowth in right ventricular cavity and obstruction of its outflow tract are described. The clinical cases showing ambiguity of disease prognosis are resulted: cardiac rhabdomyoma can not only decrease in size spontaneously and disappear even in senior school age but also cause the lethal outcome.